a) x∈ (-∞;3)
b) x∈ (-∞;0] ∪ [4;+∞)
c) x∈ (-∞;0)∪(0;2/3)
d) x∈ [-1/2;1) ∪ (1;+∞)
Объяснение:
a) f(x)=√(-x+3);
-x+3≥0; -x≥-3; x≤3.
ОО: x∈(-∞;3).
b) f(x)=√(0,5x²-2x); 0,5x²-2x≥0; x(0,5x-2)≥0;
x≥0;
0,5x-2≥0; x≥2/0,5; x≥4; x∈[4;+∞);
x≤0;
0,5x-2≤0; x≤2/0,5; x≤4; x∈(-∞;0];
OO: x∈(-∞;0] ∪ [4;+∞);
c) f(x)=ln(2/x-3);
2/x-3>0; 2/x>3; x<2/3; x∈(-∞;2/3);
x≠0; x∈(-∞;0)∪(0;+∞)
OO: x∈(-∞;0)∪(0;+∞) ∩ (-∞;2/3) ⇒ x∈(-∞;0)∪(0;2/3)
d) f(x)=√(3/(x-1)+2);
3/(x-1)+2≥0; 3+2(x-1)≥0; x≥-1/2; x∈[-1/2;+∞)
x-1≠0; x≠1; x∈(-∞;1)∪(1;+∞)
OO: x∈[-1/2;+∞) ∩ (-∞;1)∪(1;+∞) ⇒ x∈[-1/2;1)∪(1;+∞)
Объяснение:
a) x² - 2x - 15 < 0
x² + 3x - 5x - 15 > 0
x(x + 3) - 5(x + 3) > 0
(x + 3)(x - 5) > 0
x + 3 < 0 x - 5 > 0
x < -3 x > 5
x ∈ (-∞, -3) ∪ (5, +∞)
б) -x² + 6x ≥ 0
-x(x - 6) ≥ 0
x(x - 6) ≤ 0
x ≥ 0 x - 6 ≤ 0
x ≤ 6
x ∈ [0, 6]
в)
4 - x ≤ 0 5x - 2 > 0
x ≤ 4 5x > 2
x >
x ∈ (, 4]
г) x(x - 9)(x + 2) > 0
x < 0 (x - 9)(x + 2) > 0
x - 9 > 0 x + 2 > 0
x > 9 x > -2
x ∈ (-2, 0) ∪ (9, +∞)
д)
2x + 5 > 0 (x - 3)(3x + 3) ≥ 0
2x > -5 x - 3 ≥ 0 3x + 3 ≤ 0
x > x ≥ 3 3x ≤ -3
x ≤ -1
x ∈ ( , -1] ∪[3, +∞)
это первое задание
х=2.1